Reptiles - Indraneil, Das; Pui Yong, Min; Sabariman, Hassan; Taha, Wahab (UNIMAS Publisher and Natural History Publications (Borneo) Sdn Bhd, 2023)
The Bako Peninsula and its famous National Park, despite its proximity to Kuching, had received scant attention from herpetologists in the first few decades of its establishment. Starting in 1992, inventories of the reptile fauna have led to a growing list of species. The current checklist shows 62 species, as of 25 August 2022, comprising a crocodilian, four turtles, 26 lizards and 31 snakes. A total of six reptile species on Bako (five lizards and a snake) are Bornean endemics.